Banks, Shadow Banking, and Fragility - Stephan Luck; Paul Schempp (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We study a banking model in which regulatory arbitrage induces the existence of shadow banking next to regulated banks. We show that the size of the shadow banking sector determines its stability. Panic-based runs become possible only if this sector is large. Moreover, if regulated banks conduct shadow banking, a relatively larger shadow banking sector is sustainable. However, crises become contagious and spread to the regulated banking sector. We argue that deposit insurance may fail to eliminate adverse run equilibria in the presence of regulatory arbitrage. It may become tested in equilibrium if regulated banking and shadow banking are intertwined.
Keywords: G21; G23; G28; 330